A Improving Student Self-Efficacy Through the Discovery Learning Model in Islamic Religious Education - Sapna Adzhani; Totong Heri (Universitas Islam negeri Mahmud Yunus Batusangkar, 2026)
Low levels of students’ self-efficacy in Islamic Education (PAI) learning are reflected in limited classroom participation, low confidence in expressing ideas, and insufficient learning readiness. The condition indicates the need for instructional approaches that address not only cognitive achievement but also students’ psychological development. This study aims to examines the implementation of the Discovery Learning model in Pai learning and its contribution to students’ self-efficacy. The study aims to explore how Discovery Learning influences students’ learning activeness, conceptual understanding, and self-efficacy. A qualitative phenomenological approach was employed in this research. The participans consisted of Islamic Education teacher and tenth-grade students from a Muhammadiyah senior high school, selected through purposive sampling. Data were collcted using semi-structured interviews and analyzed through data reduction, thematic analysis, and interpretation of participants’ experiences. The findings reveal that the use of Discovery Learning encourages active student engagement, improves conceptual understanding, and enhances students’ self-efficacy. Increased self-efficacy is indicated by students’ greater confidence in asking questions, expressing opinions, and delivering presentations, which is influenced by mastery experiences, teacher encouragement, and emotional regulation during classroom activities. This study concludes that Discovery Learning represent a relevantinstructional alternative for PAI learning, as it supports both cognitive development and students’ psychological empowerment.